Psychological and pedagogical aspects of formation of a healthy lifestyle in the structure of the physical professional-applied preparation of future teachers (Pedagogy of Higher and Secondary Education, 2013)
Andrianov T. V. Psychological and pedagogical aspects of formation of a healthy lifestyle in the structure of the physical professional-applied preparation of future teachers.The article is devoted to the problem of formation of a healthy lifestyle in the structure of the physical professionally-applied training that affect the accumulation of specific knowledge, skills, interests, motives. An attempt is made to explore the main components of professional orientation of future teachers of physical education.
Keywords: health criteria; personality; professional activity; future teachers; physical education